Power in large buyer–small supplier relationships in sustainable supply chains - Touboulic, Anne; Chicksand, Daniel; Walker, Helen Walker (Piccola Impresa / Small Business, 2012)
This study adopts a power perspective to explore sustainable supply chain relationships and specifically uses Resource Dependence Theory (RDT) to critically analyse buyer-supplier relationships. In addition, further empirical evidence is provided extending the RDT model in this context. The concept of buyer-supplier power is explored through a qualitative study of a multinational FMCG company and agricultural growers, in the UK food industry, who work together to implement sustainable practices. The study highlights that dependence is relevant to understanding compliance in sustainable supply chains. We also show how power influences players and the sharing of sustainability-related risks and value. From a managerial perspective, the study contributes to developing a better understanding of what constitute more effective ways to manage imbalanced buyer-supplier relationships to achieve sustainability goals.